GAMBARAN PENGETAHUAN DAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI PADA PENGRAJIN DI DESA TEGALLALANG, GIANYAR TAHUN 2015 - I Putu Surya Abidharma; I Nyoman Sutarsa (E-Jurnal Medika Udayana, 2015)
DESCRIPTION OFKNOWLEDGEANDBEHAVIORINUSEPERSONAL PROTECTIVE EQUIPMENT FORCRAFTSMEN IN TEGALLALANGVILLAGE ,GIANYAR2015Tegallalang Village,Gianyar is known as the producer of handicrafts include wood crafts, paintings, handmade glass and other crafts. Based on the data obtained from the Public Health Unit Tegallalang I in 2012, 2013 and 2014, the case of accidents which consists of work accidents tend to increase. The use of personal protective equipment (PPE) is expected to minimize accidents arising out of work. This study aimed to determine the knowledge and behavior of the use of PPE. This study used a descriptive cross-sectional design with, the sample in this study were the craftsmen  in the districtTegallalang, a sample size of 100 people.Results obtained most respondents description of knowledge about the time of use, usefulness and impact when not using PPE is good, more than 50% of respondents knew the use or benefit of the use of PPE, more than 80% of respondents already knew the impact if not using PPE. The overall behavior of the use of PPE was poor with only 13% of respondents always use PPE which in this week is the most widely used mask (15%).  It could be concluded that the knowledge of the use of PPE was good but the behavior in the use of PPE was still low.